Women as hand pump technicians: empowering women and enhancing participation in rural water supply projects. Issue 3 (2nd April 2020) - Sam, Josephine-Mary; Todd, Susan K.
ABSTRACT: In rural areas of developing countries, improved access to clean water has been known to lead to reduced workloads for women and girls, and improved health and education. To sustain these benefits, women need to be active participants rather than passive beneficiaries in community projects. This article presents findings from a rural water supply programme in Ghana that actively promoted greater women's involvement. It found that training women technicians did more to galvanise their leadership potential, showcase their capabilities and make them more active participants in managing their respective village water facilities than simply including them on water management committees.